Pemodelan hidrodinamika arus pasang surut Teluk Mayalibit Kabupaten Raja Ampat Provinsi Papua Barat - Asep Sandra Budiman; Alan F. Koropitan; I Wayan Nurjaya (Depik, 2014)
Abstract. Mayalibit Bay has an unique topography due to it has only one way long canal , narrow, and devious that connecting to open sea. Study on the water mass dynamics concerning to elevation and tidal current in Mayalibit Bay was conducted by constructing the 2D numerical hydrodynamics model which was simulated for 30 days to describe the pattern of elevation and water current which was resulted from tidal processes. The 2D hydrodynamic equation was employed by finite difference methods. Validation result showed that the model has a good performance and it was relevance to in-situ measurement. The pattern of elevation and water current from many tide periods had been spatially analyzed. Generally, simulation showed that there was a significant difference between the elevation and water currents pattern inside and outside the bay during high and low tides.. Elevation and water current have higher value during highg tide (maximum 0.35 m and 0.2 m/s) than low tide period (maximum 0.14 m and 0.1 m/s ) with the velocity of water current was faster at ebb-tide or low tide. The water current in entry canal has higher value than in any part of the bay which themaximum velocity was varied from 1.6 m/s (flood-tide) to 3.7 m/s (ebb-tide). The direction of current during high tide flows was dominantly to the West-Northwest or enters the bay by following its geometric and to the East-Southeast or exits from the bay during the ebb-tidesKeywords :  Tidal; quasi-enclosed waters; numerical models; finite difference  Abstrak. Teluk memiliki topografi yang unik karena hanya memiliki satu celah atau jalur panjang, sempit, dan berkelok yang menghubungkannya dengan laut terbuka. Kajian dinamika massa air terkait elevasi dan arus pasang surut di Teluk Mayalibit telah dilakukan dengan membangun sebuah model numerik hidrodinamika 2D yang disimulasi selama 30 hari untuk menggambarkan pola elevasi dan arus akibat pasang surut. Persamaan hidrodinamika 2D diselesaikan dengan metode beda hingga. Hasil validasi menunjukkan bahwa model telah memiliki performa yang cukup baik dan relevan bila diverifikasi dengan hasil pengukuran di lapangan. Pola elevasi dan arus dalam beberapa periode pasang surut dianalisis secara spasial. Hasil simulasi menunjukkan bahwa ada perbedaan yang signifikan antara elevasi dan pola arus di dalam dan di luar teluk selama periode pasang purnama dan pasang perbani. Elevasi dan arus memiliki nilai yang lebih tinggi pada saat pasang purnama (maksimum 0,35 m dan 0,2 m/detik) dibandingkan dengan pada saat pasang perbani (maksimum 0,14 m dan 0,1 m/detik) dengan kecepatan arus yang lebih tinggi pada saat surut. Arus di jalur masuk teluk memiliki nilai yang lebih tinggi dibandingkan bagian manapun di dalam teluk, dimana kecepatan maksimumnya bisa mencapai 1,6 m/detik (pasang) sampai 3,7 m/detik (surut). Arah arus dominan di dalam teluk pada saat pasang adalah Barat - Barat Daya atau masuk ke dalam teluk mengikuti geometrinya dan ke Timur-Tenggara atau ke luar teluk pada saat surut.